'Why not you?' Discourses of widening access on UK medical school websites. Issue 6 (22nd February 2017) - Alexander, Kirsty; Fahey Palma, Tania; Nicholson, Sandra; Cleland, Jennifer
Abstract : Context: In the UK, applications to medicine from those in lower socio‐economic groups remain low despite significant investments of time, interest and resources in widening access (WA) to medicine. This suggests that medical schools' core messages about WA may be working to embed or further reinforce marginalisation, rather than to combat this. Our objective was to investigate how the value of WA is communicated by UK medical schools through their websites, and how this may create expectations regarding who is 'suitable' for medicine. Methods: We conducted a critical discourse analysis of the webpages of UK medical schools in relation to WA. Our conceptual framework was underpinned by a Foucauldian understanding of discourse. Analysis followed an adapted version of Hyatt's analytical framework. This involved contextualising the data by identifying drivers, levers and warrants for WA, before undertaking a systematic investigation of linguistic features to reveal the discourses in use, and their assumptions. Results: Discourses of 'social mobility for the individual' justified WA as an initiative to support individuals with academic ability and commitment to medicine, but who were disadvantaged by their background in the application process. This meritocratic discourse communicated the benefits of WA as flowing one way, with medical schools providing opportunities to applicants. Conversely, discourses justifying WA as an initiative to benefit patient care were marginalised and largely excluded. Alternative strengths typically attributed to students from lower socio‐economic groups were not mentioned, which implies that these were not valued. Conclusions: Current discourses of WA on UK medical school websites do not present non‐traditional applicants as bringing gains to medicine through their diversity. This may work as a barrier to attracting larger numbers of diverse applicants. Medical schools should reflect upon their website discourses, critically evaluate current approaches to encouraging applications from those in lower socio‐economic groups, and consider avenues for positive change.